Analysis of Greenhouse Gas Mitigation in Energy Sector/Electricity Sub-Sector on Street Lighting (Case Study: Palembang City) - Felicity Felicity; Dedi Rohendi; Budhi Setiawan (Program Pascasarjana Universitas Sriwijaya, 2021)
The greatest source of GHG emission from energy sector comes from fossil fuel combustion. Accordingto PLN, 63.75% of electricity distribution in South Sumatra is derived from coal combustion. Coal is a non-renewableenergy source and will deplete in a few decades. The research objective is solving problems related to energyefficiency and GHG emission reduction by reducing electricity consumption in street lighting sector. The researchmethod was carried out through SPSS statistical analysis and LEAP analysis which had been justified based onobservation on the survey results of 1,619 street lighting unit at four distribution areas of Palembang. Theimplementation of electrical energy efficiency is carried out by replacing Son T 250 W lamps into LED lamps withdifferent power. The SPSS statistical analysis determines that 1,000-unit street lightstreet lighting require lightintensity quality of 1,570 lux with correlation coefficient of 0.214. GHG mitigation was conducted in accordancewith convenience and safety standards for road users in which energy efficiency from the replacement of 3,741-unitenergy-saving lamps can reduce GHG emissions by 1,650.9138 tons of CO2e with benefit economic 2,911,481,740rupiahs. In addition, based on LEAP analysis, if 8000 units of LED lamps replace Son T lamps, the electricityconsumption of Street Lighting in 2030 will decrease with a projected efficiency of 17.48%.